Digitalization of higher education: challenges, trends and prospects - Druzhinina Natalya Valeryevna; Akhmetgalina Nina Sergeevna (Interdisciplinary Science Studies, 2024)
The digitization of higher education is an integral process in modern society, where technologies become increasingly integrated into all spheres of life. This article explores current trends and challenges faced by universities in implementing digital technologies into the educational process. Special attention is paid to the prospects for development and possible ways to optimize this process.